Patterns and Treatment Strategies of Osimertinib Resistance in T790M-Positive Non-Small Cell Lung Cancer: A Pooled Analysis - Wang, Chunsheng; Zhao, Kewei; Hu, Shanliang; Li, Minghuan; Song, Yipeng (Frontiers in Oncology, 2021)
Introduction: Osimertinib resistance is inevitable. The purpose of this study was to explore the predictive value of pretreatment clinical characteristics in T790M-positive non-small cell lung cancer NSCLC patients for the resistance pattern of osimertinib during tumor progression as well as the treatment strategy. Methods: We performed a literature search in the NCBI PubMed database to identify relevant articles and completed a pooled analysis based on 29 related published studies. The relationship between clinical characteristics, EGFR mutation type, previous treatment history and the gene mutation pattern at resistance to osimertinib was analyzed. Results: A total of 38 patients were included in the pooled analysis. Patients with an initial epidermal growth factor receptor EGFR mutation status of 19 deletions were more likely to have T790M loss (HR:12.187,95%CI:2.186-67.945, p=0.004). Patients with an initial EGFR mutation of L858R were more likely to have C797S mutations (HR: 0.063, 95% CI: 0.011-0.377, p=0.002). The other factors (age, gender, ethnicity, smoking history, previous EGFR-TKI targeted therapy history, history of radiotherapy and chemotherapy) were not associated with the resistance pattern of osimertinib (all p>0.05). Conclusions: The type of EFGR mutation in T790M-positive NSCLC patients prior to treatment can predict the resistance pattern to osimertinib. This finding plays a vital role and theoretical basis in guiding clinicians to formulate treatment strategies at the early stage of treatment and rationally combine drugs to overcome EGFR-TKI resistance.